Broad Roads and Forgotten Trails of the History of Philosophy in the Philosophical Research of Andrzej J. Noras - Alechnowicz-Skrzypek, Iwona (Folia Philosophica, 2022)
Iwona Alechnowicz-Skrzypek’s aim in this article is to present Andrzej J. Noras’s approach to the history of philosophy, which he regarded as a meta-philosophical discipline. In his publications, Noras repeatedly addressed the importance and value of historical-philosophical research. Noras’s specific understanding of history of philosophy was based on a critical attitude, according to which the researcher must make an effort not omit anything and to examine his subject from different perspectives. In his research, he followed paths rarely taken by historians of philosophy, which allowed him to make noteworthy findings in neo-Kantianism, his main area of interest. He also devoted ample attention to lives and achievements of philosophers who are either little known or even entirely forgotten. Professor Andrzej J. Noras takes credit for allowing them to speak to us again.